2001
DOI: 10.1055/s-2001-17370
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Beta-1a in Children with Multiple Sclerosis is Well Tolerated

Abstract: Preliminary data indicate that weekly intramuscular injections of IFNB-1 a are well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 8 publications
0
46
0
4
Order By: Relevance
“…1,3 The European document suggested early use of DMTs to prevent relapses, accumulation of disability, and accumulation of brain damage, recommending careful clinical and MRI follow-up. 3 Similarly, the International Pediatric Multiple Sclerosis Study Group consensus statement Table 1 Demographic and clinical findings of studies a evaluating the results of interferon-b (IFN-b) and glatiramer acetate in pediatric patients with multiple sclerosis Waubant et al 16 Mikaeloff et al 17 Ghezzi et al 21 Pohl et al 19 Tenembaum and Segura 20 Ghezzi et al 21 Tenembaum et al 22 Banwell et al 23 Mikaeloff et al 24 Kornek et al 25 Ghezzi et al 21 Drug The general approach is shown in the figure.…”
Section: Results In Young Children Vs Adolescentsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,3 The European document suggested early use of DMTs to prevent relapses, accumulation of disability, and accumulation of brain damage, recommending careful clinical and MRI follow-up. 3 Similarly, the International Pediatric Multiple Sclerosis Study Group consensus statement Table 1 Demographic and clinical findings of studies a evaluating the results of interferon-b (IFN-b) and glatiramer acetate in pediatric patients with multiple sclerosis Waubant et al 16 Mikaeloff et al 17 Ghezzi et al 21 Pohl et al 19 Tenembaum and Segura 20 Ghezzi et al 21 Tenembaum et al 22 Banwell et al 23 Mikaeloff et al 24 Kornek et al 25 Ghezzi et al 21 Drug The general approach is shown in the figure.…”
Section: Results In Young Children Vs Adolescentsmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23][24][25] Data from observational studies are available in about 600 patients treated with IFN-b: 7 studies included .20 patients; 6 have a follow-up of 2 years or more.…”
mentioning
confidence: 99%
“…Experience in the pediatric population (ages 6 -18) has recently been documented by several groups. [45][46][47][48][49][50] Safety was the primary focus of these studies, and although there are reports of incidental adverse events, adult doses appear to be well tolerated if started on an initial titration schedule. Some doses used in these studies vary empirically, based on the size of the child, ranging from one-third to full adult dose.…”
Section: Pediatric Msmentioning
confidence: 99%
“…By contrast, only few studies on immunomodulatory therapy in childhood MS have been published. These mainly describe the tolerability and side effects of IFNβ-1, which are similar to those observed in adults [16,31,37,60]. In order to evaluate the efficacy of IFNβ-1 in childhood and juvenile MS, phase III clinical trials are warranted.…”
Section: Multiple Sclerosismentioning
confidence: 93%